Synthesis and Crystal Structural of 1,10-Phenanthroline Lead(II) Complex - Xie, Dong; Cheng, Hua; Bi, Wen-Jie (Asian Journal of Chemistry, 2014)
A novel lead(II) complex [Pb(phen)2(NO3)]·NO3 has been synthesized, with 1,10-phenanthroline (phen) and nitrate (NO3–) as ligands and characterized by IR spectra and single-crystal X-ray diffraction measurements. The crystal is monoclinic, space group P2(1)/n with unit cell parameters: a =16.6321(18)Å, b = 7.7550(8)Å, c = 18.0809(19)Å, a = 90º, b = 98.2880(10)º, g = 90º, V = 2307.8(4) Å3, Z = 4, Mr = 691.62, Dc = 1.991 Mg/cm3, μ = 7.366 mm-1, F(000) = 1328, T = 298(2) K, R = 0.0795, wR = 0.1980 for 4068 reflections with I > 2s(I). In the molecular structure unit, lead(II) cation is coordinated by six donor atoms.